Gravitational Waves - Γκρέκης, Δημήτρης (Open Schools Journal for Open Science, 2024)
This is a presentation on gravitational waves. Specifically, how they are created, how they “behave”, how we detect and study them and why we study them. Gravitational waves are ripples in spacetime caused by some of the most violent and energetic processes in the universe. Predicted by Albert Einstein in 1916 as part of his general theory of relativity. They were detected for the first time in 2015 by LIGO (Laser Interferometer Gravitational-Wave Observatory).